Craniofacial Brown Tumor in Patients with Secondary Hyperparathyroidism to Chronic Renal Failure: Report of Two Cases in Cipto Mangunkusumo Hospital - Diani Kartini; Maria K. Siswiandari; Gunawan Wibisana; Erwin D. Yulian; Ahmad Kurnia; Sonar S. Panigoro; Azdi Z. Albar; Muchlis Ramli (Case Reports in Oncological Medicine)
Brown tumor is a bone lesion that arises in the setting of excess osteoclast activity in hyperparathyroidism. It consists of fibrous tissue, woven bone, and supporting vasculature, while contains no matrix. The characteristic of brown-colored lesion is a result of hemosiderin deposition into the osteolytic cysts. Two cases of young women aged 26 and 29 years old, respectively, are known with a history of end-stage renal disease (ESRD). Dialysis is performed two times/week over the last 7 years. Our patients presented with an intraoral mass of the hard palate since 12 months ago and decreased body height of 10 cm. The lesion causes difficulties in swallowing and talking. Laboratory workup showed elevated parathormone or PTH (3.391 pg/mL and >5.000 pg/mL). Neck ultrasound showed enlargement of the parathyroid glands. Supporting examination to diagnose brown tumor are neck ultrasound, CT of the neck, and parathyroid sestamibi scan. We performed parathyroidectomy. Pathology revealed hyperplasia of the parathyroid. The tumor regressed significantly within 2 weeks following the surgery, and we still observe tumor regression as well as reduction in PTH level. As clinicians, we should be alert to other possible causes of bony lesions. Clinical examination, laboratory finding, and imaging present important information to diagnose brown tumor.